2013
DOI: 10.1093/dnares/dst042
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transcriptome Sequencing of Wild Halophyte Rice, Porteresia coarctata, Provides Novel Insights into the Salinity and Submergence Tolerance Factors

Abstract: Porteresia coarctata is a wild relative of rice with capability of high salinity and submergence tolerance. The transcriptome analyses of Porteresia can lead to the identification of candidate genes involved in salinity and submergence tolerance. We sequenced the transcriptome of Porteresia under different conditions using Illumina platform and generated about 375 million high-quality reads. After optimized assembly, a total of 152 367 unique transcript sequences with average length of 794 bp were obtained. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 75 publications
5
111
0
Order By: Relevance
“…Because the wild relatives of rice are adapted to different biogeographic ranges (Fig. 1a) and can tolerate many biotic and abiotic stresses [1][2][3][4][5][6] , they constitute an important reservoir for crop improvement. Strategies to harness such traits for crop improvement show clear promise, as exemplified by the introgression of bacterial blight resistance (Xa21) from the wild species Oryza longistaminata 7 .…”
mentioning
confidence: 99%
“…Because the wild relatives of rice are adapted to different biogeographic ranges (Fig. 1a) and can tolerate many biotic and abiotic stresses [1][2][3][4][5][6] , they constitute an important reservoir for crop improvement. Strategies to harness such traits for crop improvement show clear promise, as exemplified by the introgression of bacterial blight resistance (Xa21) from the wild species Oryza longistaminata 7 .…”
mentioning
confidence: 99%
“…More recent next-generation transcriptome enrichment (Garg et al, 2013) indicates a close functional overlap of submergence and salinity tolerance trait in Porteresia, as is expected of mangrove habitat plants. However, Garg et al (2013) and Sengupta and Majumder (2009) made an observation that the similarity of Porteresia transcripts to rice transcripts was not very high. Candidate gene based studies showed that a large number of Porteresia genes are similar to Rice genes.…”
Section: The Genomic and Proteomic Studiesmentioning
confidence: 64%
“…The extended families of salt-induced transcription factors reported by Garg et al, (2013) are rather significant. Most of the TFs are upregulated during salinity stress and the transcriptional activity is repressed under submergence stress (Garg et al, 2013).…”
Section: The Genomic and Proteomic Studiesmentioning
confidence: 97%
See 2 more Smart Citations